LOCALIZATION OF NON-ABELIAN FIELD IN FIVE-DIMENSIONAL BRANEWORLD MODELS - Wulandari, Dewi; Triyanta, Triyanta (JURNAL PENELITIAN SAINTIKA, 2017)
We study the localization properties of non-Abelian field in the representation of SU(2) group both in the modified Randall-Sundrum (MRS) and in the original Randall-Sundrum (RS) models. We investigate the conditions of localization for each model. We derive the equation of motion for the field. We solve the field equation corresponding to the extra dimension and analyze the localization properties of the field on the brane. We obtain that the MRS model has different field localization properties compared to the RS model. We find that non-Abelian field is localizable on the brane of the MRS model with specific conditions but the field is not localizable on the brane of the RS model.